Person-centered care during childbirth and associated factors among mothers who gave birth at health facilities in Hawassa city administration Sidama Region, Southern Ethiopia - Sewunnet Azezew Getahun; Abebaw Abeje Muluneh; Wudit Wassu Seneshaw; Sewnet Getaye Workie; Zemenu Yohannes Kassa (BMC, 2022)
Abstract Introduction Person-centered care is a pivotal component of strategies to improve the utilization of maternity care during childbirth. However, there is limited information on the level of person-centered care during childbirth in Ethiopia. Therefore, this study aimed to assess the level of person-centered care during childbirth and associated factors in Hawassa city administration health facilities Sidama region, Ethiopia. Method Institutional based cross-sectional study was conducted among randomly selected health facilities in Hawassa city administration from September 5 to October 30, 2021. A multistage sampling technique was employed to enroll the study participants. Data were collected through face-to-face interviews using a structured questionnaire. After data collection, it was checked for completeness and consistencies then coded and entered into Epi data version 4.4.2 and exported to SPSS version 25 for analysis. Descriptive statistics were generated to describe the study findings. Then simple and multivariable linear regressions were computed. All predictor variables with P-value ≤ 0.25 in the simple linear regression were fitted into the multivariable linear regression model and a P < 0.05 was considered statistically significant. Finally, the result of the study was presented in texts, tables, and figures. Result The mean score of person-centered care during childbirth in Hawassa city was 56 with 95% of CI: [55.1, 57] and with SD ± 11.2. Giving birth at private health institutions (β = 4.3, 95% CI: (2.37, 6.22) and childbirth which was attended by a care provider who had provided ANC for mothers initially (β = 5.48, 95% CI: 3.15, 7.81) had significantly higher positive betas on person-centered care during childbirth. However, mothers who didn't get a formal education (β = -3.00, 95% CI: (-5.27, -.73) and mothers with a dead pregnancy outcome (β = -7.04, 95% CI: -10.4, -3.66) decreases the person-centered care during childbirth. Conclusion This paper showed that person-centered care during childbirth was low compared with other studies. It shall be beneficial if the city administration health facilities implement midwife-led care to improve person-centered care during childbirth.